Acute encephalopathy associated with acute hepatitis - Reye’s syndrome - Özsoylu, Şinasi; Kanra, Güler; Bilgiç, Arman (The Turkish Journal of Pediatrics, 1969)
A case of Reye’s syndrome, diagnosed clinically and confirmed by macroscopic and microscopic examination, is presented.